Integration of Salaf Islamic Boarding School Education with Modern School Curriculum - Zuhri, Saefudin; Syamsi, Atikah (TARBIYA: Journal of Education in Muslim Society, 2023)
AbstractThis study outlines the integration of salaf Islamic boarding school education with the public school curriculum (study of Islamic boarding schools in Cirebon). The discussion of the integration of education pesantren is managed in the traditional system, while madrasas and schools are managed by the conventional system. The existence of madrasahs and schools is a strategic step for pesantren in improving their education system. The presence of madrasahs and schools does not necessarily replace the traditional education system of pesantren, but complements it. Madrasahs and schools are managed with a modern system using the curriculum and always pay attention to strategic changes in responding to modernity. The framework method used in this article is field research, and the approach in this study uses a phenomenological approach and case studies with more emphasis on religious behavior. This type of research is a type of qualitative research. The results indicate that pesantren's adaptation to changing times involves curriculum revisions and the establishment of educational institutions accommodating general education needs, emphasizing the importance of integration to create well-rounded individuals capable of excelling in both religious and general sciences. Penelitian ini menguraikan integrasi pendidikan pesantren Islam Salaf dengan kurikulum sekolah umum pada pesantren di Cirebon. Pembahasan tentang integrasi pendidikan pesantren dikelola dalam sistem tradisional, sementara madrasah dan sekolah dikelola oleh sistem konvensional. Keberadaan madrasah dan sekolah merupakan langkah strategis bagi pesantren dalam meningkatkan sistem pendidikannya. Keberadaan madrasah dan sekolah tidak selalu menggantikan sistem pendidikan tradisional pesantren, melainkan melengkapinya. Madrasah dan sekolah dikelola dengan sistem modern menggunakan kurikulum dan selalu memperhatikan perubahan strategis dalam merespons modernitas. Metode kerangka yang digunakan dalam artikel ini adalah penelitian lapangan, dan pendekatan dalam penelitian ini menggunakan pendekatan fenomenologis dan studi kasus dengan penekanan lebih pada perilaku keagamaan. Jenis penelitian ini adalah jenis penelitian kualitatif. Hasil penelitian menunjukkan bahwa adaptasi pesantren terhadap perubahan zaman melibatkan revisi kurikulum dan pembentukan lembaga pendidikan yang mengakomodasi kebutuhan pendidikan umum, menekankan pentingnya integrasi untuk menciptakan individu berkepribadian baik yang mampu unggul dalam ilmu agama dan umum.How to Cite: Zuhri, S., Syamsia, A. (2023). Integration of Salaf Islamic Boarding School Education with Modern School Curriculum. TARBIYA: Journal of Education in Muslim Society, 10(1), 103-116. doi:10.15408/tjems.v10i1. 35967.